Connecting myself with the English World through e-pals - Timbe Castro, Lucy Cecilia; Matute Calle, Brenda Eulalia
The teaching methods and techniques used in the English traditional education do not allow students be involved with the last technological advances. Therefore, it is necessary to try other classroom strategies incorporating technology. This is the reason why our purpose Is to execute an intervention project in "San Diego" Educational Unit of Azogues city. This project will permit the students develop the skill of written communication worldwide using the computer technology. E-mails will make possible the integral practice of the foreign language.